The Effect of Lemongrass Aromatherapy on Sleep Quality in Perimenopausal Women - Tiara Blessenzeqi; Nila Widya Keswara (International Forum of Researchers and Lecturers, 2026)
Sleep disturbances are a common complaint among perimenopausal women due to hormonal, psychological, and physiological changes, which impact their health and quality of life. Safe and easy-to-apply non-pharmacological approaches, such as lemongrass aromatherapy (Cymbopogon citratus), have the potential to be a supportive alternative in overcoming sleep disturbances during this phase. However, empirical evidence regarding the effect of lemongrass aromatherapy on the sleep quality of perimenopausal women is still limited, especially in the context of primary health care in Indonesia. This study aims to analyze the effect of lemongrass aromatherapy on the sleep quality of perimenopausal women. This study used a quantitative approach with a one-group pretest–posttest pre-experimental design. The sample consisted of 30 perimenopausal women selected using total sampling technique in the working area of Pustu Paring Lahung UPT Tumpung Laung. The intervention in the form of lemongrass aromatherapy through inhalation was carried out regularly before bedtime. Sleep quality was measured before and after the intervention using a standardized questionnaire. Data analysis was performed descriptively and bivariately using Fisher's Exact Test. Descriptively, there was an improvement in sleep quality after the administration of lemongrass aromatherapy, marked by a decrease in the proportion of poor sleep quality and an increase in good sleep quality. However, the statistical test results showed that the relationship between sleep quality before and after treatment was not statistically significant (p = 0.515). Lemongrass aromatherapy showed a tendency toward clinically significant improvement in sleep quality, but this was not statistically significant. Further research with a stronger design and longer intervention duration is needed to confirm the effectiveness of lemongrass aromatherapy on the sleep quality of perimenopausal women.